Pt Nanoparticles with Enhanced Deaminase‐like Activity: Example of Oxidative Deamination of 5‐Hydroxymethylfurfurylamine and Glutamic Acid. Issue 5 (5th April 2022) - Lancien, Antoine; Heuson, Egon; Dumeignil, Franck; Itabaiana, Ivaldo; Froidevaux, Renato; Wojcieszak, Robert
Abstract: Oxidative deamination is part of the metabolic pathways of amino acid oxidase and glutamate dehydrogenase enzymes, and enables obtaining α ‐keto acid from amino compound with ammonia as a by‐product. This work presents the utilization of Pt‐based catalyst composed of small platinum nanoparticles supported on industrial silica support (Pt/SiO2 ). This nanozyme was tested in the oxidative deamination reaction of two amino compounds: 5 ‐hydroxymethylfurfurylamine (HMFA) to 5‐hydroxymethylfurfural (HMF) and glutamic acid (GA) to α ‐ketoglutaric acid (KGA). This paper outlines the use of Pt nanozymes with deaminase‐like activity. We showed the ability of this nanozymes to be selective and active in liquid phase oxidative deamination of HMFA and glutamic acid in a 6 to 9 pH range at 60 °C under atmospheric pressure. Pt/SiO2 nanozyme actually plays as a deaminase mimic with high HMFA conversion (60%) and cumulative yield to the corresponding desaminated keto compounds (67%). Abstract : An enzyme‐mimetic nanozyme system is reported that significantly promotes the oxidative deamination of primary amines. This work gives an example of the valorization of 5 ‐hydroxymethylfurfurylamine and glutamic acid, and could be applied to any amino acid after an optimization of the reaction conditions.